The Effect of Compensation and Motivation on Employee Turnover at PT Indofood CBP Sukses Makmur Tbk. Snack Division - Astuti, Widia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examined the impact of salary and motivation on employee turnover in the Snack Division of PT Indofood CBP Sukses Makmur Tbk., using a quantitative causal design with a census sample of 120 employees. The results revealed that salary and motivation significantly and positively affect turnover, as shown by t-test values (t_count = 9.134 for salary, t_count = 4.024 for motivation) and a significance level of 0.000 (< 0.1). Additionally, the combined effect of salary and motivation on turnover was significant, with F_count = 43.333 surpassing F_table = 3.07. The findings highlight the critical role of compensation and motivation in influencing turnover.